Sequence analysis of the shelterin telomere protection complex genes in dyskeratosis congenita. Issue 4 (5th January 2011) - Savage, Sharon A; Giri, Neelam; Jessop, Lea; Pike, Kristen; Plona, Teri; Burdett, Laurie; Alter, Blanche P
Abstract : Background: Dyskeratosis congenita (DC) is an inherited bone marrow failure syndrome characterised by dystrophic nails, abnormal skin pigmentation and oral leukoplakia. Patients are at very high risk of cancer and other medical problems. They have exceedingly short telomeres for their age and approximately 60% have a germline mutation in a gene important in telomere biology ( DKC1, TERC, TERT, TINF2, NOP10, or NHP2 ). The shelterin complex consists of six proteins encoded by TINF2, ACD, POT1, TERF1, TERF2 and TERF2IP, which are essential for telomeric stability. TINF2 mutations are present in 11–25% of patients with DC. Methods: Bi-directional sequence analysis was conducted of all exons, intron–exon boundaries and the proximal promoter of the other five shelterin genes to determine whether mutations in these genes were associated with DC. Sixteen mutation-negative patients, nine with DC and seven patients with short telomeres and bone marrow failure, were evaluated. Results: Two variants were identified, ACD Ex1+189 G→A and TERF1 Ex9+59 G→A, which were each present in one patient and a healthy parent but absent in 364 controls. Three other variants were rare (<1%) but present in both patients and controls. Discussion: These data suggest that except for TINF2, mutations in shelterin genes are not a common cause of DC.